Granular hydrogels for 3D bioprinting applications. Issue 3 (15th July 2020) - Cheng, Wei; Zhang, Jing; Liu, Ji; Yu, Ziyi
Abstract: Granular hydrogels are the conglomerations of micrometer‐sized hydrogel particles that have recently become promising in tissue growth and three‐dimensional (3D) bioprinting. Recent advances in the use of jamming transition of granular hydrogels represent a potential paradigm shift in the extrusion‐based 3D bioprinting. These dynamic granular hydrogels are shear thinning and self‐healing, enable higher printing performance, and the creation of better physiological conditions for heterocellular constructs. Here, we review the current efforts to explore materials to produce granular hydrogels with novel functional properties, focusing on the granular hydrogels that can be used for supporting baths and bioinks in the extrusion‐based 3D bioprinting. The recent advances, benefits, and challenges in this emerging area are highlighted. Abstract : Granular hydrogels are the conglomerations of micrometer‐sized hydrogel particles with impressive properties such as biocompatible, self‐healing, and shear‐thinning. In this review, the authors discuss how current challenges of three‐dimensional (3D) bioprintings could be addressed by using granular hydrogels, acting as either novel supporting baths or printable bioinks.